Immunomodulatory effects of xanthan gum in LPS-stimulated RAW 264.7 macrophages. (1st August 2017) - Liu, Fuyan; Zhang, Xiaofeng; Ling, Peixue; Liao, Joshua; Zhao, Mingsheng; Mei, Li; Shao, Huarong; Jiang, Peng; Song, Zhigang; Chen, Qixin; Wang, Fengshan
Highlights: Immunomodulatory effects of xanthan gum (XG) in macrophages were evaluated. XG ameliorates morphological alteration of LPS-stimulated RAW264.7 macrophages. XG inhibits inflammatory mediators stimulated by LPS at the mRNA and protein levels. XG has a high binding affinity to TLR4 as assessed using SPR analysis. Abstract: In this study, we evaluated the immunomodulatory effects of xanthan gum (XG) in RAW264.7 macrophages and the underlying molecular mechanisms. We used scanning electron microscopy (SEM) to analyze the morphology of XG-treated RAW264.7 cells with and without lipopolysaccharide (LPS) stimulation and investigated the subsequent effects on nitric oxide (NO), interleukin-1β (IL-1β), interleukin-6 (IL-6), tumor necrosis factor (TNF-α), inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX-2) levels in LPS-activated mouse RAW264.7 macrophages. We also analyzed the binding affinity of XG to Toll-like receptor 4 (TLR4) with surface plasmon resonance (SPR) analysis and observed that XG decreased NO, IL-6 and TNF-α secretion into the culture medium and iNOS and COX-2 protein levels induced by LPS. This study reveals a two-way immunomodulatory effect of XG on inflammatory mediators in RAW264.7 macrophages that may involve the TLR4 signal pathway, providing a pharmacological basis for the use of XG in the control of inflammatory disorders.